2012
DOI: 10.1089/cbr.2012.1224
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy with 131I-Bevacizumab as a Specific Molecule for Cells with Overexpression of the Vascular Endothelial Growth Factor

Abstract: Bevacizumab is a humanized monoclonal antibody that inhibits vascular endothelial growth factor A and is used for the treatment of several cancers. We labeled this monoclonal antibody with Iodine-131 (¹³¹I) and performed in vitro quality control and tumor cell growth inhibition tests. Bevacizumab was labeled with ¹³¹I using chloramine T. Radiochemical purity and stability in phosphate-buffered saline and human blood serum were determined using thin-layer chromatography and radio-sodium dodecyl sulfate-polyacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Untreated and treated thyroid cancer and HFFF2 cells were subjected to cell proliferation assay using MTT to quantify the metabolic activity to cleave tetrazolium salts [25, 26]. Cells (20,000) were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Untreated and treated thyroid cancer and HFFF2 cells were subjected to cell proliferation assay using MTT to quantify the metabolic activity to cleave tetrazolium salts [25, 26]. Cells (20,000) were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The MTT test is based on the strength of mitochondrial enzymes to decrease MTT (pale yellow) to formazan crystals (dark blue). Owing to their impenetrability through the cell membrane, formazan crystals collect in cells (Ashrafi et al , 2012 ). Cells (20,000) were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The second study showed higher CD138 expression in all cancer types compared to healthy ovarian tissue, without any correlation in terms of chemoresistance or exposure to estrogens ( 11 ). Therefore, we considered CD138 as a potential innovative target antigen for the treatment of ovarian cancer by RIT, in the same way as other emerging targets such as Her2 ( 29 ) or VEGF ( 30 ). This choice was strengthened by the results that we obtained in this study on CD138 expression and RIT.…”
Section: Discussionmentioning
confidence: 99%